A DIFFERENTIATED APPROACH TO RECONSTRUCTIVE SURGERY IN PATIENTS WITH DIABETIC FOOT SYNDROME: // Collection of abstracts of the scientific and practical conference «Current Problems of Surgical Soft Tissue Infections» (2024), Tashkent, October 28 - Sattarov, I.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
The immediate results (up to 3 months) in the comparison group (n = 62) showed that the traditional approach to reconstructive plastic surgery in patients with DFS in 70.9% of cases (p> 0.05) leads to primary healing of the postoperative wound. Purulent complications in the postoperative period occurred in 8.1% (p> 0.05). The appearance of neurotrophic ulcers on the operated foot soon was noted in 21.0% of cases (p> 0.05). In the neuropathic form of DFS, neurotrophic changes were more common than in the neuroischemic form – 84.6 and 15.4%, respectively.